2012
DOI: 10.1016/j.neuroscience.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Strength–duration relationship for intra- versus extracellular stimulation with microelectrodes

Abstract: Highlights► The excitability time constant chronaxie for electrical stimulation is analyzed. ► Chronaxie varies along the neural axis. ► Extracellular stimulation with microelectrodes causes short chronaxies. ► In some cases strength–duration curves have a bimodal shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 56 publications
5
66
0
Order By: Relevance
“…This is consistent with predictions from computational modelling [30], [31] and with previous studies involving epiretinal electrical stimulation of retinal ganglion cells in other species (e.g. rat, guinea pig and monkey retinae: [32], rabbit retina: [33]).…”
Section: ) Waveform Parameterssupporting
confidence: 92%
“…This is consistent with predictions from computational modelling [30], [31] and with previous studies involving epiretinal electrical stimulation of retinal ganglion cells in other species (e.g. rat, guinea pig and monkey retinae: [32], rabbit retina: [33]).…”
Section: ) Waveform Parameterssupporting
confidence: 92%
“…Studies in the central nervous system (CNS) reported that sodium channels of the type Nav1.6 which are located in the band region have lower thresholds than Nav1.2 type channels that are located in somatic and dendritic parts, respectively (Hu et al (2009)). For stimulation in the CNS using micro electrodes close to the soma or even further away from the actual band region this means that the AIS is likely to be the site of spike initiation (Rattay and Wenger (2010); Rattay et al (2012)). We do not know yet if this special sodium channel distribution also can be of relevance in the stimulation of retinal ganglion cells.…”
Section: Discussionmentioning
confidence: 99%
“…The curvature of the strength–duration function depends on the TMS pulse shape and the membrane dynamics of the neurons directly depolarized by the TMS electric field (Rattay et al, 2012). To parameterize the strength–duration curve, the neural membrane can be approximated as a low-pass filter with time constant τ m (Barker et al, 1991; Corthout et al, 2001; Lapicque, 1907).…”
Section: Methodsmentioning
confidence: 99%